Analysis of the effectiveness of different cardioprotection methods in mitral valve repair in low left ventricular ejection fraction - D.V. Shabanov; O.A. Loskutov; B.M. Todurov (Медицина неотложных состояний)
Background. Currently, cold crystalloid cardioplegia (CCC) is used in approximately 85–90 % of cardiac surgeries requiring myocardial protection during cardiopulmonary bypass (CB). According to literature data, the rate of complications associated with this method ranges from 10 to 15 %, with the most common complications being low cardiac output syndrome and arrhythmias. The aim of our study was to analyze the effectiveness of artificial electrical fibrillation of the heart and Bretschneider solution in mitral valve repair surgeries in patients with low left ventricular (LV) ejection fraction (EF) under СВ. Materials and methods. This prospective cohort study included 97 patients with LV EF < 40 % and mitral valve stenosis or insufficiency who underwent mitral valve repair surgery at the Heart Institute of the Ministry of Health of Ukraine (Kyiv) under CB. Depending on the cardioprotection method used, all patients were divided into two groups: group A (46 people) — artificial electrical fibrillation, and group B (51 participants) — CCC using Bretschneider solution. Data collection and analysis included preoperative (anthropometric, biochemical, echocardiographic data, presence of comorbidities), intraoperative (duration of anesthesia, CB, and aortic cross-clamping, need for inotropic support), and early postoperative parameters (echocardiography, troponin I levels on the first postoperative day, and presence of rhythm disturbances). Results. Patients in group A had significantly shorter duration of anesthesia (p < 0.0001), СВ (p < 0.0001), and total aortic cross-clamping (p < 0.0001) compared to group B. On the first postoperative day, group A patients had a significantly higher troponin I level versus group B, by 33.30 ± 4.27 % (p = 0.001). Additionally, group A showed a 7.98 ± 1.44 % lower LV EF (p = 0.047) on the first postoperative day compared to group B. Furthermore, one-way ANOVA revealed a significant reduction in LV EF versus baseline values in group A during the hospital stay (p = 0.011), which was not observed in group B. Conclusions. Patients undergoing artificial electrical fibrillation exhibited significantly higher troponin I levels (by 33.30 ± 4.27 %, p = 0.001) compared to those receiving ССС, along with a significant reduction in EF compared to baseline values (p = 0.011).